A Social Performance Management Framework for Islamic Microfinance Institutions - Abdul Khalid, S. N.; Sheikh Kamaruddin, S. (Universiti Sains Islam Malaysia, 2024)
The Islamic microfinance industry is in its infancy and it faces various challenges, including the lack of social performance management tools customised to the specific nature of the industry. Even though managing the performance of microfinance institutions has gained momentum with the development of several tools and techniques, the existing tools are inadequate for addressing the needs of IMFIs. Hence, this paper seeks to conceptualise a social performance management framework that is appropriate for IMFIs, to help them accomplish their financial, social and spiritual mission. It is argued that the spiritual dimensions and elements should be integrated into IMFI's social performance management systems, specifically in their mission statement, governance structure, internal systems and activities, as well as in their measures of output and impact.